BMI and breast cancer in upper Egypt - Abeer F Amin (Wolters Kluwer Medknow Publications, 2016)
Background and aim BMI may be an important factor affecting breast cancer outcome. Materials and methods The present study included 100 patients who were newly diagnosed with breast cancer at Assiut University Hospital. Their BMI was measured, and the relation of BMI to the stage of breast cancer and age was determined. Results Patients' ages ranged from 27.0 to 72.0 years. Overall, 45% of the patients were between the ages of 50 and 60 years, and their mean age was 50.6 years. Stage I, II, III, and IV breast cancer were diagnosed in 14, 64, 12, and 10% of the patients, respectively. Around 29% of the patients were overweight and 35% of them were obese. There was a significant positive correlation between age and BMI (P = 0.000). In addition, there was a significant positive relation between BMI and the stage of breast cancer at diagnosis, with a statistical significant difference (P < 0.05). Conclusion Overweight and obese breast cancer patients were more often older, and this was significantly associated with later stages at diagnosis.